Effects of dietary supplementation with omega-3 fatty acid-rich linseed on the reproductive performance of ewes in subtropical climates - Akhtar, P.; Rajoriya, J. S.; Singh, A. K.; Ojha, B. K.; Jha, A. K.; Bisen, A.; Bajaj, Nitin K.; Ahirwar, M. K.; Raje, A.; Singh, A. P.; Peepar, S. S.; Mishra, A. K.; et al. (Frontiers in Veterinary Science, 2024)
The present study evaluated the effects of omega-3 (ω-3) fatty acid-rich linseed supplementation on the reproductive performance, endocrine profile, and biochemical profile of ewes reared in subtropical climates. Forty-eight acyclic and clinically healthy Marwari sheep, aged 1.5–2.5 years with no parity, were divided into four groups (n = n = 12 in each). Ewes in the control group (group I) were fed only a basal feed, whereas ewes in the treatment groups II, III, and IV were fed the basal diet along with 10%, 15%, and 20% linseed, respectively, daily on a dry matter basis. The experiment was conducted during the typical breeding season (October–November) of the sheep. The estrus induction rate was significantly higher (p < 0.05) in all treatment groups than in the control group. The estrus induction interval was significantly lower (p < 0.05) in group III. The conception rate in group I was significantly lower (p < 0.05). In addition, ewes in the control group had a significantly lower (p < 0.05) lambing rate than all treatment groups. Serum progesterone concentrations differed significantly (p < 0.05) between the control and the treatment groups on days 15, 30, 45, and 60 of supplementation. On treatment days 15 and 30, the serum estrogen concentrations were significantly higher (p < 0.05) in all treatment groups compared to that in group I. In all treatment groups, monounsaturated fatty acid (MUFA) decreased significantly (p < 0.05), whereas polyunsaturated fatty acid (PUFA) increased significantly (p < 0.05) from day 15 onward. In conclusion, by providing 15% dietary linseed supplementation to ewes, their reproductive performance can be improved in subtropical climates. Future studies are recommended to further elucidate the role of linseed supplementation in sheep reproduction in subtropical climates.